The transition to a data economy in financial services - Fryczak, Jan Makary (Przejście do gospodarki opartej na danych w usługach finansowych, 2020)
The aim of the article is to identify the opportunities and challenges in the field of data processing faced by companies providing financial services in Poland. Half of the world’s consumers are surrounded by data collection devices. Financial services are becoming increasingly aware of the need to change to enter this new data-driven economy. This transformation is a complex process that will require the best management skills to be successful. Obviously, companies should remain as innovative as possible, but at the same time they cannot devote all their resources to investments in technology. This article reviews the literature on the current developments in data-driven technologies to provide an outline of the environment to which financial firms need to adapt. The author describes the sources from which data can be obtained, and gives examples of opportunities they create, namely autonomous cars, geolocation and targeted advertising, as well as offers insights into the challenges of data processing and the transition to a data economy
Financial Sciences. Nauki o Finansach, 2020, vol. 25, no. 4, s. 43-54
Keywords: Big Data; Internet of Things; datafication; technological change; internet rzeczy; danetyzacja; zmiana technologiczna